How hormones, vertical jump and perceived exertion change in clutch time. A season case study of an amateur basketball team - Izquierdo, J. M.; Redondo, J. C.; Marqués-Jiménez, D.; Zarauz-Moreno, A.; Fernández-Lázaro, D. (International Journal of Performance Analysis in Sport, 2024)
Basketball clutch time is defined as minutes when the scoring margin is within 5 points with five or fewer minutes remaining in a game. Our aims were to explore the relations and to compare testosterone and cortisol behaviours, vertical jump (CMJ) and perceived exertion (RPE) between clutch time games (CT) and non-clutch time games (N-CT); during a season in an amateur male team (24.02 ± 3.36 years). Data was collected at 22 games considering CT (n = 8) or N-CT (n = 14) depending on the scoring margin with five or fewer minutes. A total of 120 player cases who participated in the last 5 min of each game (CT, n = 48; N-CT, n = 72) were analysed using a mixed linear model for repeated measures to compare the CT and N-CT variations. The main results were Cortisol, CMJ and RPE means turned out to be higher in CT, but relevant differences were only identified for RPE (ES = 0.69). Findings suggested that clutch performance was often viewed through players` subjective parameters. Consequently, we recommend that both players and coaches consider it for CT performance. In addition, we extend current basketball CT indicator knowledge opening future research and applied practice.